インドヨウ ノ フユウセイ アメーバ - 羽田, 良禾; ハダ, ヨシネ; HADA, Yoshine (国立極地研究所, 1969)
P(論文) Marine amoebae are rarely found among planktonic organisms, and no naked form of oceanic Protozoa has ever been obtained. An interesting marine pelagic amoeba was detected in the plankton samples, which were taken from the surface water of the Indian Ocean and the South China Sea during the voyage of the 5th Japanese Antarctic Research Expedition (1960-61). The examined amoeba has a nucleus and a few contractile vacuoles in the main body, and a number of uroids at the posterior end in the creeping form. In general outline, it is allied to Trichamoeba pallida SCHAFFER, a nitric marine amoeba, but specific identification is impossible due to lack of data on living specimens departmental bulletin paper